2022
DOI: 10.3390/pr10020180
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Starch Binary Mixtures with Cordia and Ziziphus Gums

Abstract: The effect of gum Cordia (GC) and gum Ziziphus (GZ) on the physicochemical properties of wheat, potato, and chickpea starches was investigated. Native or acetylated gums were mixed with starch at 2% or 5%. Starches were analyzed using rapid viscoanalyzer (RVA), differential scanning calorimeter (DSC), texture analyzer, and rheometer. In the presence of gums, the data showed clear variations between the starch gels. The effects of gum acetylation on the starch characteristics were significant. According to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…In the case of ZG, the gum appears to have inhibited granule swelling by covering the surface of the starch granules, resulting in a lower PV. We previously reported that when CG and ZG were combined with pure starch, the PV increased [ 17 ]. When compared to the PV in wheat flour, which was reported here, the PV of pure starch reported by Mohamed et al, (2022) dropped from 2970 cP to 1886 cP as shown in Figure 1 , which could be due to gluten interference or dilution of the starch with the gluten.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of ZG, the gum appears to have inhibited granule swelling by covering the surface of the starch granules, resulting in a lower PV. We previously reported that when CG and ZG were combined with pure starch, the PV increased [ 17 ]. When compared to the PV in wheat flour, which was reported here, the PV of pure starch reported by Mohamed et al, (2022) dropped from 2970 cP to 1886 cP as shown in Figure 1 , which could be due to gluten interference or dilution of the starch with the gluten.…”
Section: Resultsmentioning
confidence: 99%
“…Gum Cordia (GC) and gum Ziziphus (GC) were extracted according to the methods described in another study carried out by the same research group [29]. To prevent enzymatic browning, cardia or ziziphus fruits were destoned, carefully washed, and steamed for 3 min.…”
Section: Isolation Of Gumsmentioning
confidence: 99%
“…By elevating the starch gelatinization temperature, xanthan and guar gums, for example, were shown to increase batter viscosity, but pectin and cellulose derivatives (HPMC) decreased it [54]. We previously reported that both GC and GZ gums increased the gelatinization temperature of wheat starch [29], implying that an increase in cake volume would be predicted in the presence of GC and GZ gums; however, the data did support this hypothesis with respect to loaf volume but not the specific volume. The fact that the gelatinization temperature of wheat starch had no influence on cake volume is remarkable because neither gum created a higher specific cake volume than the control.…”
Section: Bread and Cake Quality Evaluationmentioning
confidence: 99%
“…The dough matrix is a combination of two phases: a continuous phase of high molecular weight glutenin held by disulfide linkages, which impart the elastic nature, and a discontinuous phase developed by low molecular weight gliadin, which imparts the viscose nature. The added gums, due to their lower molecular weight compared to glutenin, align themselves with the discontinuous phase of the dough and contribute to balancing the elasticity and extensibility [ 33 ]. Doughs with lesser extensibility are considered better for cookie preparation, while more elastic dough is favorable for bread preparation, where a higher gas volume needs to be incorporated and retained by the gluten network [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%